Point-of-Care Ultrasound for Critical Care - Sun-Jung Lim; Shailaja Hayden; Patricia Kritek; Richard Fagley; Matthew Hallman; Dana Sajed; David Park; Robert Zierler; Amy Morris (Association of American Medical Colleges, 2013)
Abstract This is a resource for bedside ultrasound training. It outlines a two-day workshop designed to teach fundamental bedside ultrasound skills to critical care providers. Each day consists of two didactic sessions and four practical (hands-on) stations. Day One. Didactics: The Basics of Ultrasound and Vascular Access, Thoracic Ultrasound. Hands-on stations: "Knobology" - How the Ultrasound Machine Works, Vascular Access, Normal Chest, Thoracic Pathology. Day Two. Didactics: Limited Echocardiography, Deep Vein Thrombosis (DVT)Assessment. Hands-on stations: Limited Echocardiography Parasternal View, Apical View, Subcostal View, and Lower Extremity DVT Assessment. This resource contains all the files needed to conduct a similar two-day workshop, including: Needs assessment survey. All didactic powerpoint presentations, including images and videos. Specific goals and objectives for each hands-on station. Pre- and post-tests to assess learners. Course evaluation forms. Pocket card outlining the steps for limited echocardiography. Additional references for self-study. Point-of-care ultrasound use is increasing and the critical care literature supports its use for procedural guidance as well as the evaluation of shock states. As such, many critical care fellowship programs want to incorporate ultrasound training into their training programs. Some faculty members and fellows have received formal ultrasound training, (e g., intensivists who have taken a certificate course through the American College of Chest Physicians) but the majority have not. At our institution, ultrasound training has largely been informal, with the exception of using ultrasound to guide central venous access. In addition, ultrasound examinations are usually performed by residents and fellow trainees in the traditional "See one. Do one. Teach one" model. This course builds upon informal workshops used to train critical care fellows in the use of bedside ultrasound, and was developed to teach faculty members the basics of point-of-care ultrasound as a first step in creating a comprehensive bedside ultrasound curriculum for critical care providers. We created a multidisciplinary group of instructors from Emergency Medicine, Pulmonary and Critical Care Medicine, Anesthesiology Critical Care, Radiology and Cardiology to develop and implement the curriculum, to ensure consistency across all specialties using bedside ultrasound at our institution. Using this course we trained 38 pulmonary and critical care faculty (Winter 2011-2012), over four half-day workshops, and approximately 12 anesthesiology and critical care faculty (Spring 2011-2012). We will be repeating the workshop for our critical care fellows in the fall of 2012, and will offer the course again for faculty later in the 2012-2013 academic year.